2013
DOI: 10.1088/0067-0049/209/1/2
|View full text |Cite
|
Sign up to set email alerts
|

THE BOLOCAM GALACTIC PLANE SURVEY. X. A COMPLETE SPECTROSCOPIC CATALOG OF DENSE MOLECULAR GAS OBSERVED TOWARD 1.1 mm DUST CONTINUUM SOURCES WITH 7.°5 ⩽ l ⩽ 194°

Abstract: The Bolocam Galactic Plane Survey (BGPS) is a 1.1 mm continuum survey of dense clumps of dust throughout the Galaxy covering 170 square degrees. We present spectroscopic observations using the Heinrich Hertz Submillimeter Telescope of the dense gas tracers, HCO + and N 2 H + 3 − 2, for all 6194 sources in the Bolocam Galactic Plane Survey v1.0.1 catalog between 7.5 • ≤ l ≤ 194 • . This is the largest targeted spectroscopic survey of dense molecular gas in the Milky Way to date. We find unique velocities for 31… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(114 citation statements)
references
References 61 publications
4
110
0
Order By: Relevance
“…Dunham et al (2011b) observed 631 BGPS sources within narrow ranges in Galactic longitude, while the new data presented in this work observed BGPS clumps that were detected in dense gas tracer HCO + 3-2 and had T pk (HCO + ) > 0.3 K from Schlingman et al (2011) and Shirley et al (2013). All new observations were targeted with the center pixel of the K-band Focal Plane Array (KFPA) toward the S 1.1 mm flux density peak in the BGPS v2.0 maps (Ginsburg et al 2013).…”
Section: New Gbt Nh 3 Observationsmentioning
confidence: 49%
See 3 more Smart Citations
“…Dunham et al (2011b) observed 631 BGPS sources within narrow ranges in Galactic longitude, while the new data presented in this work observed BGPS clumps that were detected in dense gas tracer HCO + 3-2 and had T pk (HCO + ) > 0.3 K from Schlingman et al (2011) and Shirley et al (2013). All new observations were targeted with the center pixel of the K-band Focal Plane Array (KFPA) toward the S 1.1 mm flux density peak in the BGPS v2.0 maps (Ginsburg et al 2013).…”
Section: New Gbt Nh 3 Observationsmentioning
confidence: 49%
“…HCO 3 2 ( ) (see Shirley et al 2013). Figures 12(b) shows the distributions of observed NH 3 linewidth, indicating a factor of two increase from 1.339±0.014 km s −1 on median toward starless candidates to 2.736±0.03 km s −1 on median toward UCH II associated clumps.…”
Section: Gas Kinetic Temperature and Line Widthmentioning
confidence: 95%
See 2 more Smart Citations
“…Since the Hi-GAL data convey information only on the continuum emission, we investigated the literature to search for molecular or recombination line observations of the 204 usable targets. In particular, we refer to the following articles: Urquhart et al (2013b; hereafter URQ13), Anderson et al (2009Anderson et al ( , 2012, Beuther et al (2002), Shirley et al (2013), Bronfman et al (1996), Jones et al (2012), Kolpak et al (2003), Pandian et al (2008), Sewilo et al (2004), Watson et al (2003), Wienen et al (2012), and the red MSX source (RMS) database 2 (Lumsden et al 2013). We were able to assign an LSR velocity to all but four (G011.9786-00.0973, G026.0083+00.1369, G026.8304-00.2067, and G065.2462+00.3505) of the 204 sources.…”
Section: Distance Estimatesmentioning
confidence: 99%